Early–middle Holocene relative sea-level oscillation events recorded in a submerged speleothem from the Yucatán Peninsula, Mexico. (September 2015) - Moseley, Gina E; Richards, David A; Smart, Peter L; Standish, Christopher D; Hoffmann, Dirk L; ten Hove, Harry; Vinn, Olev
Geomorphological and biological archives of relative sea-level change in the western North Atlantic-Caribbean region following the Last Glacial Maximum have traditionally supported the hypothesis of a punctuated rise towards the present sea level. Such records, however, are often at insufficient resolution to discern centennial-scale changes. In caves where the water table is closely controlled by sea level, active periods of speleothem growth constraining maximum sea level, used in combination with marine overgrowths constraining minimum sea level, are a promising alternative archive recording sea-level variability at higher resolution. Here, we present a U-Th-dated early–middle Holocene speleothem record from a submerged cave on the tectonically stable Yucatán Peninsula, Mexico. Our record shows that polychaetes (Annelida, Polychaeta) colonised a sub-aerially deposited stalagmite during four individual submergence events. Submergence events occurred at approximately 8.9, 8.6, 8.4 and 6.0 ka, which we attribute to previously unrecognised minor sea-level oscillation events (OE1–OE4) above and below −6.12 ± 0.1 m relative to present sea level (r.s.l.). Combining these results with mangrove-derived relative sea-level constraints from another submerged cave on the Yucatán Peninsula, we are able to suggest that OE1 and OE2 did not reach as high as −5.26 m r.s.l., but that OE3 and OE4 exceeded −5.22 m r.s.l. We conclude that subsidence of the North American ice-load bulge was the main cause of relative sea-level rise. Superimposed on the glacio-isostatic adjustment were periods of widespread northern hemisphere cooling and ice margin re-advance, resulting in a relative sea-level fall on four occasions during the early–middle Holocene.